Reconsidering the Effective Factors on Development of Agricultural Tourism and Entrepreneurship Survey in Rural Areas (Case Study: Villages of Tehran Province) - afshin bahmani; mojtaba ghadirimasoom; mahdi hajiloo; farideh azimi; mahdieh ghadirimasoom (تحقیقات کاربردی علوم جغرافیایی)
Today, agricultural tourism or agritourism is emphasized by focusing on a farm or agricultural business as a tourist destination with the goal of educational, recreational and job creation in rural areas. This type of tourism is a stimulus for the vulnerable rural economy and the needs of citizens who pay for their visits to or participation in farm activities, the direct purchase of agricultural products, and the familiarization with nature and indigenous people, which contribute to economic prosperity, job creation and prosperity. Villages will be. In the present study, its nature is applied and its method is descriptive-analytical, the explanation and identification of the factors affecting the development of rural tourism in rural areas is the goal of the research. The statistical population of the study consisted of three groups of officials and experts, locals and tourists. For each group, according to the Cochran formula, 34, 261 and 20 subjects were selected. The main focus of the data on the field method was collected through face-to-face questionnaires and interviews. To analyze the data, descriptive statistics methods such as mean and frequency and inferential statistics methods such as one-sample t-test, Chi-square and Chi-square, and Kruskal-Wallis were used. The findings show that factors such as housing provision for tourists, government incentive schemes, coordination between government agencies, awareness of farmers, and setting up private sector investment with a significant level of 0.30 and a positive amount of chi-square are the most important priorities. Effective in developing agricultural tourism in rural areas of Tehran province.